Recombinant Production and One-Pot Purification for Enhancing Activity of Haloacid Dehalogenase from Bacillus cereus IndB1 - Enny Ratnaningsih; Sulistiya Nirta Sunaryo; Idris Idris; Rindia Maharani Putri (Reaktor, 2021)
In recent years we have witnessed the emergence of organohalogen utilization in various chemical-based industries, particularly polymer-based, agricultural, and pharmaceutical sectors. Despite this, organohalogen compounds are actually very dangerous to the environment, as they are difficult to be naturally degraded and generally toxic to organisms. A green and biocompatible method to overcome this issue is by employing enzymes that could convert organohalogens into non-toxic compounds, such as the class of enzymes known as haloacid dehalogenases. To enhance the activity of haloacid dehalogenase isolated from local strains of Bacillus cereus IndB1, we have developed a recombinant expression system using pET-bcfd1 plasmid in E. coli BL21 (DE3) host cells. Following enzyme production, we also demonstrated a one-pot purification system for the expressed dehalogenase, harnessing the presence of His-tag in the recombinant clones. Purification was carried out using Ni-NTA affinity column chromatography, using imidazole eluent with a concentration gradient of 10 mM to 500 mM. The enzyme activity was tested against the monochloroacetic acid (MCA) substrate according to the Bergmann and Sanik method, and the protein content in the solution was measured using the Bradford method. The purity of the enzyme after one-pot purification was confirmed by SDS-PAGE analyses, showing a single band of 40 kDa in size. Remarkably, the purified haloacid dehalogenase specific activity was increased by 12-fold compared to its crude enzyme extract. Therefore, the expression and purification system developed in this study allow further exploration of dehalogenases from local strains as an efficient catalyst for MCA biodegradation.Keywords: recombinant expression, haloacid dehalogenase, monochloroacetic acid, enzyme purification